Pelatihan Pemanfaatan Tanaman untuk Meningkatkan Produksi Susu dan Kesehatan Ternak Kambing Senduro Di Lumajang - Kuswanti, Nur; Ducha, Nur; Fudhaili, Ahmad; Nafisah, Wirdatun; Purnama, Erlix Rakhmad; Aprilia, Rizka Muizzu; Warman, Adi Tiya; Aritonang, Heni Natalia (Universitas Negeri Padang, 2025)
Senduro goats are a leading local dairy livestock commodity in Lumajang Regency. To increase goats’ milk production and health, the farmers still need additional knowledge and skill about forage standards. This Community Service activity aims to increase farmers' knowledge about the use of local plants to increase the milk production and the health of Senduro goats in Lumajang, as well as to improve their skills in providing feed. The activity used lectures, discussions, and demonstrations. The data of training participants’ knowledge were obtained through pre- and post-tests. Participants’ response were obtained using a questionnaire. The results showed that overall participants’ knowledge about the use of local plants to increase milk production and the health of Senduro goats increased. The clarity of the material delivery, the demonstration of feed formulations, and the implementation were stated to be very good. In addition, the participants hoped that the activity would continue.